Biological maturation, training experience, body size and functional capacity of adolescent female basketball players: A Bayesian analysis. Issue 5 (October 2018) - Leonardi, Thiago J; Paes, Roberto R; Breder, Larissa; Foster, Carl; Gonçalves, Carlos E; Carvalho, Humberto M
In the present study we examined the age- and maturity-associated variation on body size and functional capacities in 47 adolescent female basketball players. Also, we examined the relative contribution of growth and maturity status to functional capacity between player variation. Data included chronological age, age at menarche, years of training experience; body dimensions; countermovement jump, Line drill test and Yo-Yo intermittent recovery test – level 1. Bayesian multilevel modelling was used to estimate the independent effects of age, maturity status, years of training experience and body size on functional capacity indicators. Players were, on average, advanced in maturity status, with a mean age at menarche of 11.20 years (1.32 years). Age-associated variation in age at menarche, body size and functional performance was present. No substantial maturity-associated variation was observed for stature and functional capacities, but late maturing players appeared to be less experienced in the sport. Variance partition coefficients ranged between 38% and 45% for the three indicators of functional capacities. Body mass and adiposity were the predictors identified for all indicators of performance. Maturity status and years of experience were predictors of performance in the countermovement jump while age and years of experience were predictors of performance for the Line drill. Stature was only identified as a predictor of the Yo-Yo intermittent recovery – level 1. Coaches should interpret functional performance in adolescent female basketball players considering their different ages (chronological, biological and accumulated training) and their influence on body dimensions.